Treatment patterns and burden of myelosuppression for patients with small cell lung cancer: A SEER‐medicare study. (2022) - Epstein, Robert S.; Nelms, Jerrod; Moran, Donald; Girman, Cynthia; Huang, Huan; Chioda, Marc
Abstract: Purpose: To depict the treatment journey for patients with small cell lung cancer (SCLC) and evaluate health care resource utilization (HCRU) associated with myelosuppression, a complication induced by chemotherapy or chemotherapy plus radiation therapy. Patients and methods: This was a descriptive, retrospective study of patients with SCLC aged ≥65 years, identified from linked Surveillance, Epidemiology, and End Results (SEER)-Medicare data curated between January 2012 and December 2015. Treatment types (chemotherapy, radiation therapy, surgery) were classified as first, second, or third line, depending on the temporal sequence in which regimens were prescribed. For each year, the proportions of patients completing 4- or 6-cycle chemotherapy regimens, with hospital admissions associated with myelosuppression, or who used granulocyte colony–stimulating factors (G-CSFs), blood/platelet transfusions, or erythropoiesis-stimulating agents (ESAs), were calculated. Results: Chemotherapy was administered as initial treatment in 7, 807/11, 907 (65.6%) patients whose treatment journey was recorded. Approximately one-third ( n  = 3, 985) subsequently received radiation therapy. In total, 5, 791 (57.8%) patients completed the guideline-recommended 4–6 cycles of chemotherapy. Among all chemotherapy-treated patients, 10, 370 (74.3%) experienced ≥1 inpatient admission associated with myelosuppression (anemia, 7, 366 [52.8%]; neutropenia, 4, 642 [33.3%]; thrombocytopenia, 2, 375 [17.0%]; pancytopenia, 1, 983 [14.2%]). Supportive care interventions included G-CSF (6, 756 [48.4%] patients), ESAs (1, 534 [11.0%]), and transfusions (3, 674 [26.3%]). Conclusion: Chemotherapy remains a cornerstone of care for patients with SCLC. Slightly over half of patients completed the recommended number of cycles, underscoring the frailty of patients and aggressiveness of SCLC. HCRU associated with myelosuppression was prominent, suggesting a substantial burden on older patients with SCLC.